2018
DOI: 10.1177/0032321717745433
|View full text |Cite
|
Sign up to set email alerts
|

Do Party Manifestos Matter in Policy-Making? Capacities, Incentives and Outcomes of Electoral Programmes in France

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 78 publications
0
34
0
Order By: Relevance
“…It is worth pointing out that we do not look at either the fulfilment of single pledges (Mansergh and Thomson, 2007) or at by-issue variation, that is, at whether some parties are more responsive to specific policy areas. Rather, we focus on the composition of the policy agenda as a whole and analyse the congruence of the distribution of attention across all policy issues in party manifestos and legislative priorities, an approach adopted also by other works (Baumgartner et al ., 2010; Bevan et al ., 2011; Persico et al ., 2012; Borghetto et al ., 2014; Froio et al ., 2016; Brouard et al ., Forthcoming).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth pointing out that we do not look at either the fulfilment of single pledges (Mansergh and Thomson, 2007) or at by-issue variation, that is, at whether some parties are more responsive to specific policy areas. Rather, we focus on the composition of the policy agenda as a whole and analyse the congruence of the distribution of attention across all policy issues in party manifestos and legislative priorities, an approach adopted also by other works (Baumgartner et al ., 2010; Bevan et al ., 2011; Persico et al ., 2012; Borghetto et al ., 2014; Froio et al ., 2016; Brouard et al ., Forthcoming).…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected using questionnaires, interview guide and documentary review guide and analyzed from completed questionnaires by the respondents which revealed varied responses as presented in Table 2.0. Brouard et al, (2018) argue that political organizations always work to influence public policy. Political party leaders quickly move to address policy issues that arise to capture public attention.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a recent study finds that promises on regulatory issues that are easily changed are most likely kept while promises on redistributive issues are more difficult to deliver (Brouard et al. ). Patterns of non‐compliance can be explained with strategic behaviour by parties who ‘measure the constraints and incentives that weigh upon policy‐making’ (Brouard et al.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of non‐compliance can be explained with strategic behaviour by parties who ‘measure the constraints and incentives that weigh upon policy‐making’ (Brouard et al. : 13). While a review of the literature on promise‐keeping suggests that strategic party behaviour is possible, the evidence on the case of homeownership and housing markets presented in this article cannot conclusively resolve this puzzle which requires more attention by future work.…”
Section: Discussionmentioning
confidence: 99%